Ag caint linn fhéin - Ó Neachtain, Joe Steve (Cló lar-Chonnacht, 2013)
A collection of talks and essays given by Joe Steve Ó Neachtain on various topics spanning about 20 years.
Description based on publisher supplied metadata and other sources